Analisis Sentimen Masyarakat terhadap Tindakan Vaksinasi dalam Upaya Mengatasi Pandemi Covid-19 - Brian Laurensz; Eko Sediyono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
Coronavirus has become a global pandemic and has spread almost all over the world, including Indonesia. Many negative impacts resulted from the spread of COVID-19 in Indonesia, so the government made vaccination measures to reduce the rate of spread of COVID-19. Responses from the public to vaccination measures are quite diverse on social media Twitter. Some are supportive and some disagree. The purpose of this study is to find out how people's sentiment towards vaccination measures. The data used 845 tweets, using two keywords,